Gambaran Pengetahuan dan Perilaku Vaksinasi HPV pada Wanita Usia Reproduktif di Kelurahan Putat Jaya - Danendra Seno Prabowo; Hanna Tabita Hasianna Silitonga; Mellyanawati Mellyanawati (SENTRI: Jurnal Riset Ilmiah, 2025)
HPV infection is caused by the Human Papillomavirus which attacks the skin and mucosa, thus causing genital warts (types 6 and 11), cervical cancer (types 16 and 18), and has the potential to develop into Squamous Cell Carcinoma (SCC), vulvar cancer, and oropharyngeal cancer. HPV vaccination is a primary prevention strategy that is mainly recommended for individuals aged 9–14 years before the initiation of sexual activity, but it can still be administered to women of reproductive age who remain at risk of HPV exposure through sexual contact. This study used a descriptive quantitative approach with observational methods and a cross-sectional design to describe the level of knowledge and behavior of HPV vaccination among women of reproductive age in Putat Jaya Village. Data collection was conducted in July–August 2025 by distributing questionnaires to 96 women of reproductive age, with sample determination using the Lemeshow formula and accidental sampling method. Analysis was conducted to determine the frequency distribution and percentage of knowledge and behavior related to HPV vaccination. The results showed that the level of respondents’ knowledge was classified as sufficient (62.5%), while vaccination behavior was still low (83.3%). This study shows that women of reproductive age in Putat Jaya Village, Surabaya, have a sufficient level of knowledge regarding HPV vaccination (60.2%), but low levels of practice (80.3%) are still seen in 60 respondents (60.2%).